“Монгол-Хятадын хүмүүнлэгийн солилцооны шинэ боломж, шинэ сорилт” эрдэм шинжилгээний симпозиум болов (Journal of International Studies, 2014)
English title: Scientific symposium with the theme of “New opportunities and challenges for the Humanitarian exchange between Mongolia and China” is held